2020
DOI: 10.1002/dta.2944
|View full text |Cite
|
Sign up to set email alerts
|

Optimization, validation, and comparison of a rapid method for the quantification of insulin‐like growth factor 1 in serum using liquid chromatography–high‐resolution mass spectrometry

Abstract: Human insulin‐like growth factor 1 (IGF‐I) is the primary mediator of the effects of the growth hormone (GH). Therefore, it has been used as a biomarker to detect the abuse of GH in sports. The measurement of IGF‐I relies on mass‐based and immunological approaches to analysis. Among the mass‐based analysis methods, liquid chromatography–mass spectrometry (LC–MS) has a number of functional advantages. LC–MS measurements based on the quantification of IGF‐I, according to trypsin digestion, are used in the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…97 These same guidelines were used by Seo et al for the validation of a method for the quantification of insulin growth factor I (IGF-I), a biomarker for GH misuse, in human serum samples using LC-HRMS following a rapid sample preparation method. 98 In this regard, they validated the linearity (correlation r 0.9994), selectivity, intra-and interday precision (CV < 2% and CV < 6% respectively), recovery (>95%), accuracy (>99%), LOQ (20 ng/mL), and LOD (15 ng/mL), and compared the method with those usually applied for detecting IGF-I, finding that their method was faster and cheaper and required a low sample volume. 98 The use of Eurachem validation guidelines was reported to determine the LOD, selectivity, and specificity of desmopressin in 10 human plasma samples and in 10 urine samples.…”
Section: Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…97 These same guidelines were used by Seo et al for the validation of a method for the quantification of insulin growth factor I (IGF-I), a biomarker for GH misuse, in human serum samples using LC-HRMS following a rapid sample preparation method. 98 In this regard, they validated the linearity (correlation r 0.9994), selectivity, intra-and interday precision (CV < 2% and CV < 6% respectively), recovery (>95%), accuracy (>99%), LOQ (20 ng/mL), and LOD (15 ng/mL), and compared the method with those usually applied for detecting IGF-I, finding that their method was faster and cheaper and required a low sample volume. 98 The use of Eurachem validation guidelines was reported to determine the LOD, selectivity, and specificity of desmopressin in 10 human plasma samples and in 10 urine samples.…”
Section: Validationmentioning
confidence: 99%
“…98 In this regard, they validated the linearity (correlation r 0.9994), selectivity, intra-and interday precision (CV < 2% and CV < 6% respectively), recovery (>95%), accuracy (>99%), LOQ (20 ng/mL), and LOD (15 ng/mL), and compared the method with those usually applied for detecting IGF-I, finding that their method was faster and cheaper and required a low sample volume. 98 The use of Eurachem validation guidelines was reported to determine the LOD, selectivity, and specificity of desmopressin in 10 human plasma samples and in 10 urine samples. 99 For human plasma samples, the LOD was established at 50 pg/mL, and additionally it was found that the method exhibited good selectivity, since an adequate separation was achieved between desmopressin, the ISs, and the carrier peptide.…”
Section: Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the concordances between the manufacturers' reference intervals and those obtained in the study were generally poor ( Chanson et al, 2016 ). An alternative to immunoassays is liquid chromatography-tandem mass spectrometry (LC-MS/MS), already used for IGF-1 quantification mainly in serum ( Ketha and Singh, 2015 , Cox et al, 2014 , Such-Sanmartín et al, 2015 , Lopes et al, 2014 , Bronsema et al, 2018 , Thevis et al, 2011 , Cox et al, 2014 , Mongongu et al, 2021 , Seo et al, 2021 , Coppieters et al, 2020 ). In particular, Bronsema et al (2018) developed and validated an LC-MS/MS targeted method for the detection of IGF-1 in serum in the 10–1000 ng/mL concentration range by selecting two signature peptides; an urea-based sample preparation procedure was proposed and no analyte enrichment step was required.…”
Section: Introductionmentioning
confidence: 99%